Mimamsa Epistemology - Choosukhserm, Thanakorn; Palako (Rai-Sa-nguan), Phramaha Saccarak; Phaengsipol, Kaenpetch (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 12 No 1 (2020): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Epistemology of Mimamsa mentioned a character of knowledge, feature, and norm of truth and falsehood including the sources or types of Pramanas which were the tool to bring the knowledge. The way of knowledge, initially, has 3 ways: perception, inference, and verbal testimony. Later, three kinds of knowledge were added: comparison, implication, and non-apprehension. The theory of Mimamsa epistemology related to rational knowledge, understanding relied on the present knowledge and rational knowledge itself. Other knowledge beyond this was not rational. This kind of knowledge was an understanding of what made by independent cause from any defect and conflict. It is said that the referred sentence and followed sentence or summarized sentence must have coherency. If that massage in two sentences did not have any conflicts, this knowledge is rational. Briefly, the Epistemology of Mimamsa has 2 kinds, namely: immediate knowledge and mediate knowledge.